Effect of inorganic oxides on heat resistance of fluorosilicone rubber - FENG Xiao-ya, WEI Kai-jie, HU Yan-jie (Hecheng xiangjiao gongye, 2024)
The effects of self-made nano particles titanium dioxide (TiO2) and iron-doped titanium dioxide (TiO2/Fe2O3) as heat-resistant additives on thermal stability and tensile properties of fluorosilicon rubber after hot air aging were studied. The decomposition products of fluorosilicon rubber at 5% weight loss in air and the content of characteristic groups of fluorosilicon rubber before and after thermal aging were analyzed. The effects of commercial heat-resistant additives, such as nano ceria (CeO2), ferric oxide (Fe2O3) and aluminum trioxide (Al2O3) on fluorosilicone rubber were compared. The results showed that when the mass fraction of nano heat- resistant additive was 2%, the 5% weight loss temperature of fluorosilicone rubber in air from high to low was TiO2/Fe2O3, TiO2, Fe2O3, CeO2, Al2O3 samples and blank sample. The 5% weight loss temperature of fluorosilicone rubber with nano-TiO2/Fe2O3 heat-resistant additive reached 453 ℃, which was 47 ℃ higher than that of blank sample. Nano-TiO2/Fe2O3 heat-resistant additive could significantly inhibit oxidation of fluorine-containing side groups of fluorosilicone rubber, which was the main reason for improvement of the heat resistance of fluorosilicone rubber.